EFL STUDENT’S APOLOGY WHEN COMING LATE TO THE CLASSROOM - Finda Muftihatun Najihah (Jurusan Sastra Indonesia, 2019)
This research investigates the apology’s utterances performed by EFL students when they are coming late to the classroom. The politeness theory of Lakoff and the elements of Apology proposed by Smith are used as the basis for approaching this topic. This research is conducted to deeply describe (1) the kinds of elements of apology found in students’ utterance of apology and (2) how the elements of apology represent the politeness principles. It utilizes descriptive qualitative research since it is conducted to obtain a deep and detailed analysis of the object, which is in the form of utterances and words. The data is taken from the students of Faculty of Humanities majoring in English Language and Letters Department in Maulana Malik Ibrahim State Islamic University, Malang. The results demonstrate that there are at least 3 elements found and maximumly 6 elements involved. Students generally realize that what they are doing suffered other party but the utterances do not fully mean apologizing even some indicate good apology. Further, it enables to conclude that modesty maxim of politeness principle is the dominant maxim found in this study. The politeness principle is well represented by the elements of apology found in the students’ utterances.